Spatial tumor immune heterogeneity facilitates subtype co-existence and therapy response in pancreatic cancer - Lukas Klein; Mengyu Tu; Niklas Krebs; Laura Urbach; Daniela Grimm; Muhammad Umair Latif; Frederike Penz; Anna Blandau; Xueyan Wu; Rebecca Diya Samuel; Stefan Küffer; Florian Wegwitz; et al. (Nature Communications)
Abstract Pancreatic ductal adenocarcinoma (PDAC) displays a high degree of spatial subtype heterogeneity and co-existence, linked to a diverse microenvironment and worse clinical outcome. However, the underlying mechanisms remain unclear. Here, by combining preclinical models, multi-center clinical, transcriptomic, proteomic, and patient bioimaging data, we identify an interplay between neoplastic intrinsic AP1 transcription factor dichotomy and extrinsic macrophages driving subtype co-existence and an immunosuppressive microenvironment. ATAC-, ChIP-, and RNA-seq analyses reveal that JUNB/AP1- and HDAC-mediated epigenetic programs repress pro-inflammatory signatures in tumor cells, antagonizing cJUN/AP1 signaling, favoring a therapy-responsive classical neoplastic state. This dichotomous regulation is amplified via regional TNF-α+ macrophages, which associates with a reactive phenotype and reduced CD8+ T cell infiltration in patients. Consequently, combined preclinical anti-TNF-α immunotherapy and chemotherapy reduces macrophages and promotes CD3+/CD8+ T cell infiltration in basal-like PDAC, improving survival. Hence, tumor cell-intrinsic epigenetic programs, together with extrinsic microenvironmental cues, facilitate intratumoral subtype heterogeneity and disease progression.